Development of biodegradable coating by using biopolymer anti corrosive reagent / Iling Aema Wonnie Ma - Iling , Aema Wonnie Ma (2017)
Biopolymer nanofiller is an approachable reinforcement agent of emerging interest to protect metals against corrosion due to its ability as a renewable, biodegradable and biocompatible polymer resource in the earth. In this study, a series of nanocomposites based on nanocellulose (NC) and nanochitosan (NCH) with an undiluted clear difunctional bisphenol A/epichlorohydrin derived liquid epoxy resin (EP) were prepared and applied on mild steel under room temperature. Furthermore, the composition was cured with isophorone diamine with a constant ratio of 70:30 for all systems. Each system consists of neat epoxy with 1.0 wt.%, 1.5 wt.% and 2.0 wt.% of epoxy/nanocellulose (ENC) nanocomposites and 0.5 wt.%, 1.0 wt.% and 2.0 wt.% of epoxy/nanochitosan (ECH) nanocomposites. The thickness of the dry film was measured by using coating thickness gauge and found to be about 60 ± 5 μm for all systems. Nanofiller and nanocomposite samples were characterized by X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Fourier transform infrared (FTIR). The thermophysical properties of the nanocomposites were determined using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Moreover, the transparency of the nanocomposite specimens was examined by UV-vis spectroscopy at a range of 300 - 800 nm. Corrosion protection properties of coated mild steel substrate in 3.5 wt.% NaCl solution was comparatively studied by Electrochemical impedance spectroscopy (EIS) for 30 days. The anticorrosion performance of nanocomposite contains with 1.0 wt.% of NC and 0.5 wt.% of NCH contents revealed the most pronounced anticorrosion performance and also influenced the degradation, thermal stability and transparency of coating film. In accordance with that, all the results showed that the nanocomposite coatings with nanofiller noticeably influenced the epoxy-diamine liquid pre-polymer, both physically and chemically.